2004
DOI: 10.1242/jeb.00820
|View full text |Cite
|
Sign up to set email alerts
|

In situcardiac performance of Pacific bluefin tuna hearts in response to acute temperature change

Abstract: This study reports the cardiovascular physiology of the Pacific bluefin tuna (Thunnus orientalis) in an in situ heart preparation. The performance of the Pacific bluefin tuna heart was examined at temperatures from 30°C down to 2°C. Heart rates ranged from 156·beats·min -1 at 30°C to 13·beats·min -1 at 2°C. Maximal stroke volumes were 1.1·ml·kg -1 at 25°C and 1.3·ml·kg -1 at 2°C. Maximal cardiac outputs were 18.1·ml·kg -1 ·min -1 at 2°C and 106·ml·kg -1 ·min -1 at 25°C. These data indicate that cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 63 publications
3
105
0
Order By: Relevance
“…A further mechanism could be a reduction in enzymatic efficiency at lower temperatures, leading to higher aerobic costs and increased thermogenesis. Cooler temperatures are also associated with bradycardia, which may result in lowered cardiac output and reduced rates of oxygen delivery to the digestive tissues, and consequently a lower rate of food metabolism (Blank et al, 2004). Our results also indicate that there may be an interaction between ambient temperature and diet; we found that temperature had a larger effect on HIF for sardine meals than for squid meals, although this interaction was not significant.…”
Section: Discussionmentioning
confidence: 43%
“…A further mechanism could be a reduction in enzymatic efficiency at lower temperatures, leading to higher aerobic costs and increased thermogenesis. Cooler temperatures are also associated with bradycardia, which may result in lowered cardiac output and reduced rates of oxygen delivery to the digestive tissues, and consequently a lower rate of food metabolism (Blank et al, 2004). Our results also indicate that there may be an interaction between ambient temperature and diet; we found that temperature had a larger effect on HIF for sardine meals than for squid meals, although this interaction was not significant.…”
Section: Discussionmentioning
confidence: 43%
“…Both the aerobic scope (e.g. Brett, 1962;Ultsch et al, 1980;McKenzie et al, 2012;Eliason et al, 2013a;Killen et al, 2014;Del Raye and Weng, 2015) and ƒ H (Stillman, 2002;Blank et al, 2004;Braby and Somero, 2006;Franklin et al, 2007;Sidhu et al, 2014;Chen et al, 2013;Verhille et al, 2013;Anttila et al, 2014;Ferreira et al, 2014) measurements have been reinstituted to investigate the thermal niches of fishes in this era of rapid climate change. We tested the hypothesis that the cardio-respiratory system of B. saida would thermally acclimate at 0.5, 3.5 and 6.5°C.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal sensitivity of the tuna heart may therefore limit the niche occupied by tunas [6]. Indeed, cooling causes bradycardia and an associated reduction in cardiac output in bluefin and yellowfin (T. albacares) tunas [7,8]. However, the Pacific bluefin tuna heart generates greater contractile force and maintains cardiac rhythm at colder temperatures than its tropical sister taxa [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cooling causes bradycardia and an associated reduction in cardiac output in bluefin and yellowfin (T. albacares) tunas [7,8]. However, the Pacific bluefin tuna heart generates greater contractile force and maintains cardiac rhythm at colder temperatures than its tropical sister taxa [7,9]. Understanding cardiac thermal sensitivity in the tunas may help to delineate the key steps that protect cardiac function in the cold.…”
Section: Introductionmentioning
confidence: 99%